Szegénység és társadalmi kirekesztettség a mai Magyarországon - Havasi, Éva (Szociológiai Szemle, 2024)
The paper analyses multi-dimensional poverty also called exclusion with the help of a large national sample. The paper shows the long-term trends covering three decades of increasing income inequalities, the decade-long decrease and slow upturn of personal incomes, and the changes in various poverty measures. The second part offers an approach to multiple deprivation or exclusion as the simultaneous presence of various aspects of objective and subjective poverty, and gives an account of the situation of the families that may be considered excluded. The third part analyses the dynamics of poverty as a lifetime and as a shorter-term experience, and also the future expectations of the poor. The conclusion is that there is a small and not very visible group split off the ’first society’ that, without public help is condemned to lasting exclusion.